Molecules - Atkins, P. W. (Peter William) 1940-; Atkins, Peter William 1940-.; Atkins, Peter 1940-. (New York Scientific American Library, 1987)
In this book, you will meet the molecules that make sugar sweet, that make soap soapy, and that give rise to the brilliant palette of colors unveiled in autumn foliage. You will see molecules that can quell pain and alleviate depression as well as those that can induce addiction and wreak havoc on our environment. You will unravel the chains that nature and industry weave to link small molecules into the giant molecules of silk and its synthetic imitations. Lavishly illustrated and elegantly written, Molecules requires no prior knowledge of chemistry. P .W. Atkins lucidly portrays the structures of the substances that make up our everyday world and our daily experiences, showing their shapes, their interrelations, why they behave as they do, and how they carry out their tasks. He helps us comprehend the extraordinary economy and variety of nature.
Includes index.
Bibliography: p. 183-186.
Keywords: Molecular structure; Molecules; Structure moleculaire